Epigallocatechin-3-gallate and related phenol compounds redirect the amyloidogenic aggregation pathway of ataxin-3 towards non-toxic aggregates and prevent toxicity in neural cells and Caenorhabditis elegans animal model. (15th June 2017) - Visentin, Cristina; Pellistri, Francesca; Natalello, Antonino; Vertemara, Jacopo; Bonanomi, Marcella; Gatta, Elena; Penco, Amanda; Relini, Annalisa; De Gioia, Luca; Airoldi, Cristina; Regonesi, Maria E.; Tortora, Paolo
Abstract: The protein ataxin-3 (ATX3) triggers an amyloid-related neurodegenerative disease when its polyglutamine stretch is expanded beyond a critical threshold. We formerly demonstrated that the polyphenol epigallocatechin-3-gallate (EGCG) could redirect amyloid aggregation of a full-length, expanded ATX3 (ATX3-Q55) towards non-toxic, soluble, SDS-resistant aggregates. Here, we have characterized other related phenol compounds, although smaller in size, i.e. (−)-epigallocatechin gallate (EGC), and gallic acid (GA). We analysed the aggregation pattern of ATX3-Q55 and of the N-terminal globular Josephin domain (JD) by assessing the time course of the soluble protein, as well its structural features by FTIR and AFM, in the presence and the absence of the mentioned compounds. All of them redirected the aggregation pattern towards soluble, SDS-resistant aggregates. They also prevented the appearance of ordered side-chain hydrogen bonding in ATX3-Q55, which is the hallmark of polyQ-related amyloids. Molecular docking analyses on the JD highlighted three interacting regions, including the central, aggregation-prone one. All three compounds bound to each of them, although with different patterns. This might account for their capability to prevent amyloidogenesis. Saturation transfer difference NMR experiments also confirmed EGCG and EGC binding to monomeric JD. ATX3-Q55 pre-incubation with any of the three compounds prevented its calcium-influx-mediated cytotoxicity towards neural cells. Finally, all the phenols significantly reduced toxicity in a transgenic Caenorhabditis elegans strain expressing an expanded ATX3. Overall, our results show that the three polyphenols act in a substantially similar manner. GA, however, might be more suitable for antiamyloid treatments due to its simpler structure and higher chemical stability.